Modèles médiévaux de l’amitié masculine - William Burgwinkle (Itinéraires)
It is easy to forget, in reading Michel Foucault on friendship, that much of his inspiration and many of his sources came from the early Middle Ages. Foucault echoes Thomas Aquinas, Peter of Blois, and earlier Stoic thinkers in setting up friendship as a complicated relation to God and the self that both disciplines the self and gives one access to higher truths – spiritual and sensual. Yet this thinking is hardly visible in many medieval texts outside the realm of theology. Except for the elevated realm of romance, in which heroes bathe in each other’s affection, friendship can be a conflicted, even deadly, business, and the bond between the partners more often resembles a sadistic or masochistic relation than one that relies on perfect clarity and reciprocity. Daurel et Beton offers a stirring example of such a text, one that complicates the idealism of Foucault and the theologians but offers its own twisted version of wisdom and truth.